Factors contributing to radiation dose for patients and operators during diagnostic cardiac angiography. Issue 1 (28th November 2018) - Crowhurst, James A.; Whitby, Mark; Savage, Michael; Murdoch, Dale; Robinson, Brendan; Shaw, Elizabeth; Gaikwad, Niranjan; Saireddy, Ramkrishna; Hay, Karen; Walters, Darren L.
Abstract: Introduction: Diagnostic coronary angiography (CA) uses ionising radiation with relatively high doses, which impact on both patients and staff. This study sought to identify which patient and procedural factors impact patient and operator dose the most during CA. Methods: Patient and procedure related variables impacting on Kerma area product (PKA ) and operator dose (OD) were collected for 16 months. Procedures were separated into 10 different procedure categories. PKA was used for patient dose and OD was measured with an instantly downloadable dosimeter (IDD) – downloaded at the end of each procedure. High and low radiation dose was defined by binary variables based on the 75th percentile of the continuous measures. Univariate and multivariate regression were used to identify predictors. Results: Of 3860 patients included, the IDD was worn for 2591 (61.7%). Obesity (BMI > 30 compared to BMI < 25) was the strongest predictor for both a PKA (odds ratio (OR) = 19.1 (95% CI 13.5–26.9) P < 0.001) and OD (OR = 3.3 (2.4–4.4) P < 0.001) above the 75th percentile. Male gender, biplane imaging, the X‐ray unit used, operator experience and procedure type also predicted a high PKA . Radial access, male gender, biplane imaging and procedure type also predicted a high OD. Conclusion: Radiation dose during CA is multifactorial and is dependent on patient and procedure related variables. Many factors impact on both PKA and OD but obesity is the strongest predictor for both patients and operators to receive a high radiation dose. Abstract : Radiation dose during cardiac angiography is harmful to both patients and staff. This study measured radiation dose to patients and primary operators. Radiation dose was compared across multiple variables that would impact on radiation dose. The study demonstrated that radiation dose is dependent on multiple variables but patient obesity was the strongest predictor for a high radiation dose for patients and operators.